2022
DOI: 10.33964/jp.v31i1.569
|View full text |Cite
|
Sign up to set email alerts
|

Preferensi dan Adopsi Petani terhadap Varietas Unggul Baru Padi di Provinsi Jawa Tengah

Abstract: Peningkatan produksi padi dapat dilakukan dengan menerapkan inovasi teknologi, salah satunyavarietas unggul baru padi (VUB). Penelitian dilaksanakan untuk menganalisis tingkat preferensi dan tingkatadopsi petani terhadap VUB Inpari 32, Inpari 42 dan Inpari 43. Penelitian dilaksanakan pada bulan Julisampai November 2020, melalui survei dan observasi lapang terhadap 90 petani di Kabupaten Pemalangdan Tegal. Analisis data dilakukan secara deskriptif dan analisis Mann-Whitney U test. Hasil penelitianmenunjukkan ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Rice, serving as the primary dietary staple for over 50% of the global population and a majority in Indonesia, occupies a critical nexus at the confluence of agricultural practices, environmental conservation, and public health. Ardiwinata and Nursyamsi's (2012) research, conducted in the rice production hub of Central Java, revealed pesticide residues in all sampled rice, underscoring the pervasive presence of these contaminants. The prevalent use of pesticides in conventional farming, while a widespread practice, has inadvertently contaminated this essential food source.…”
Section: Introductionmentioning
confidence: 91%
“…Rice, serving as the primary dietary staple for over 50% of the global population and a majority in Indonesia, occupies a critical nexus at the confluence of agricultural practices, environmental conservation, and public health. Ardiwinata and Nursyamsi's (2012) research, conducted in the rice production hub of Central Java, revealed pesticide residues in all sampled rice, underscoring the pervasive presence of these contaminants. The prevalent use of pesticides in conventional farming, while a widespread practice, has inadvertently contaminated this essential food source.…”
Section: Introductionmentioning
confidence: 91%
“…Beberapa VUB padi yang potensial dikembangkan di lahan pasang surut adalah Inpari-33, Inpari-47, Inpari-48, dan Logawa. VUB Inpari-33 memiliki potensi hasil mencapai 9.8 ton/ha dengan rata-rata hasil 6.6 t/ha, VUB Inpari-47 memiliki potensi hasil mencapai 9.52 t/ha dengan rata-rata hasil 7.71 t/ha, dan VUB Inpari-48 memiliki potensi hasil mencapai 9.13 t/ha dengan rata-rata hasil 7.64 t/ ha (Sastro et al, 2021), Sedangkan VUB Logawa memiliki potensi hasil mencapai 7.15 t/ha dengan ratarata hasil 6.8 t/ha (Romdon et al, 2014). Beberapa VUB ini dapat dijadikan alternatif pengganti VUB padi Inpara-3.…”
Section: Pendahuluanunclassified
“…planting to harvesting, depending on the type of variety and the environmental conditions in which the rice grows. Technological developments in the food sector produce various kinds of premium-quality rice and rice varieties resistant to global climate change caused by global warming [6]. Rice plants can be distinguished based on their varieties.…”
Section: Study Areamentioning
confidence: 99%
“…Technological developments in the food sector produce various kinds of premium-quality rice and rice varieties resistant to global climate change caused by global warming [6]. Rice plants can be distinguished based on their varieties.…”
Section: Introductionmentioning
confidence: 99%